Comparative analysis of agricultural holdings in Romania by size classes - Alesandra Marina Manolache (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The approach regarding the comparative analysis of the performance of agricultural holdings is represented by the current level of development of the national economy, in order to achieve the evolution of agricultural holdings in Romania. This paper is based on the comparative analysis of statistical data from a quantitative and qualitative point of view, highlighting agricultural holdings and their utilized agricultural area, in order to perform a comparative analysis between the size classes of the area by categories. of use. The purpose of this paper is to identify solutions to increase the number of medium sized farm.
Keywords: Q10; Q15; 330; farms; areas; agricultural